Contemporary Families: An Equity Lens - Elizabeth B. Pearce (Linn-Benton Community College, 2020)
This openly licensed text, created with students, approaches contemporary families from an equity lens. It asks two questions relevant to the Difference, Power, and Discrimination outcomes at Linn-Benton Community College and Oregon State University: “What do families need?” and “How do society and institutions support or get in the way of families getting what they need?" Original content is licensed under CC BY, except as otherwise noted. More specific information can be found under Licenses and Attributions at the bottom of each section. Print copy: https://www.lulu.com/en/us/shop/elizabeth-pearce/contemporary-families/paperback/product-rjq8mm.html